PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU BERBASIS ENTREPREUNER DI SMP N 1 SINGOROJO - Kuncoro Pujiwarto; Ngurah Ayu Nyoman; Endang Wuryandini (STKIP Subang, 2023)
This study aims to determine: The objectives to be achieved in this study are to: a. Analyzing the role of the principal as a manager in improving teacher performance based on entrepreneurship at SMP Negeri 1 Singorojo, b. Analyzing the role of the principal as a supervisor in improving teacher performance based on entrepreneurship at SMP Negeri 1 Singorojo. This research is a type of research with a qualitative approach. The informants of this study were the principal as the research subject, vice principal, teachers, students and committee members of SMP N 1 Singorojo. Data collection techniques used interviews, observation and documentation, while data analysis techniques used Data Condensation. The results of the research show that: a. Principals can create an atmosphere of creative performance by coming up with innovative ideas through digital-based learning programs according to the stated vision, namely;